Japanese Deep Sea Impact Experiment (JET) And Its Preliminary Results - Katsuya Tsurusaki (International Marine Minerals Society, 1996)
Commercial mining of manganese nodules is expected to begin within the next 20 to 50 years in large areas of abyssal sea floor in the Pacific Ocean. While deep sea mining is expected to realize significant quantities of rare metals that are needed for modern technology, the mining operation will cause extensive resedimentation over large areas of deep sea floor, the effects of which are thought to be harmful to the benthic community. Our present knowledge of deep sea benthic ecology is so limited that we cannot predict the magnitude of the impact. In November 1994, the United Nations Convention on the Law of the Sea was enforced and giving added impetus to improving our understanding of the effects of future mining operations. In order to fully understand the impact of deep sea mining and to mitigate the harmful environmental effects, it is necessary to accumulate more information on the deep sea environment and benthic communities. To achieve these objectives and to understand the relationship between resedimentation and biological reaction, artificial impact experiments are being conducted by the USA and Germany. The former named BIE (Benthic Impact Experiment) began in 1991 and is being performed by NOAA (National Oceanic and Atmospheric Administration of the United State of America) in the North Equatorial Pacific Ocean. The latter named DISCOL (Disturbance and Recolonization Experiment in the Deep South Pacific Ocean) was started in 1989 and is being conducted in the South Equatorial Pacific Ocean by a scientific group from Hamburg University. The Metal Mining Agency of Japan (MMAJ) is also carrying out environmental studies. These studies, commenced in 1989, are being conducted in association with NOAA and include an experiment named the Japan Deep Sea Impact Experiment (JET).